2019
DOI: 10.1038/s41746-019-0179-9
|View full text |Cite
|
Sign up to set email alerts
|

Language impairment in adults with end-stage liver disease: application of natural language processing towards patient-generated health records

Abstract: End-stage liver disease (ESLD) is associated with cognitive impairment ranging from subtle alterations in attention to overt hepatic encephalopathy that resolves after transplant. Natural language processing (NLP) may provide a useful method to assess cognitive status in this population. We identified 81 liver transplant recipients with ESLD (4/2013–2/2018) who sent at least one patient-to-provider electronic message pre-transplant and post-transplant, and matched them 1:1 to “healthy” controls—who had similar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 35 publications
0
18
0
Order By: Relevance
“…Most interestingly, Dickerson et al used natural language processing (a branch of artificial intelligence used by Amazon's Alexa, Apple's Siri, and Google Assistant), and a paired Wilcoxon signed-rank test to find that patients with MELD ≥ 30 (model for endstage liver disease score) had decreased word length and fewer 6+ letters words before liver transplant compared to after liver transplant. Similarly, the sentence length decreased following liver transplant [56].…”
Section: Existing Application Of Artificial Intelligence To Mhe Diagnosismentioning
confidence: 90%
See 1 more Smart Citation
“…Most interestingly, Dickerson et al used natural language processing (a branch of artificial intelligence used by Amazon's Alexa, Apple's Siri, and Google Assistant), and a paired Wilcoxon signed-rank test to find that patients with MELD ≥ 30 (model for endstage liver disease score) had decreased word length and fewer 6+ letters words before liver transplant compared to after liver transplant. Similarly, the sentence length decreased following liver transplant [56].…”
Section: Existing Application Of Artificial Intelligence To Mhe Diagnosismentioning
confidence: 90%
“…As mentioned above, artificial intelligence can explore such changes in multidimensional data obtained either by the recording of handwriting or speech [56,58]. The first step of the proposed algorithm would be extracting features characterizing the underlying patterns of the speech or handwriting signals using signal processing algorithms.…”
Section: Outlook For the Further Application Of Artificial Intelligence To Mhe Diagnosismentioning
confidence: 99%
“…( 61 ) Dickerson et al conducted an interesting study of using NLP to analyze electronic messages from patients with cirrhosis, and suggested that longer sentences with shorter words predicted the presence of HE. ( 62 )…”
Section: Natural‐language Processingmentioning
confidence: 99%
“…The app, developed by Bajaj et al [40,65], has shown good sensitivity and specificity in detecting minimal hepatic encephalopathy compared with established measures. Other recent work has piloted examining National Language Processing from patient communications within their electronic health records in relation to transplant outcomes [66]. Although significantly more work is needed in validating these approaches, they do provide innovative spaces for future research into identifying those at risk for cognitive impairments and associated negative outcomes.…”
Section: Cutting Edge Assessment and Pursuit Of The Elusive Gold Stan...mentioning
confidence: 99%